2016
DOI: 10.1111/cch.12330
|View full text |Cite
|
Sign up to set email alerts
|

The role of collaboration in the cognitive development of young children: a systematic review

Abstract: Background: Collaboration is a key facilitator of cognitive development in early childhood;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 50 publications
0
18
0
2
Order By: Relevance
“…Their study of 6- and 7-year-old children’s CPS with peers in sorting tasks found that only children with lower sorting abilities showed significant sorting improvement when partnered with higher ability peers and that “explaining” problem-solving (talking out loud) with their partner improved this ability. A systematic review of collaboration and cognitive development in young children found low-ability students benefitting the most from tasks requiring visual perception and problem-solving and highlighted the need for discussion and feedback throughout CPS processes for all students (Sills et al , 2016). There is no definitive agreement on how development impacts CPS, however, researchers generally agree that CPS interventions can help develop related skills in all children and teachers can significantly assist with this endeavor (Lai, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their study of 6- and 7-year-old children’s CPS with peers in sorting tasks found that only children with lower sorting abilities showed significant sorting improvement when partnered with higher ability peers and that “explaining” problem-solving (talking out loud) with their partner improved this ability. A systematic review of collaboration and cognitive development in young children found low-ability students benefitting the most from tasks requiring visual perception and problem-solving and highlighted the need for discussion and feedback throughout CPS processes for all students (Sills et al , 2016). There is no definitive agreement on how development impacts CPS, however, researchers generally agree that CPS interventions can help develop related skills in all children and teachers can significantly assist with this endeavor (Lai, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A systematic review by Chang and Locke (2016) [ 25 ] concluded that the inclusion of peers was one of the most promising strategies for social skills intervention. A recent review [ 26 ] concluded that collaborative learning activities are particularly beneficial for low-ability children at younger ages (4–7 years old).…”
Section: Introductionmentioning
confidence: 99%
“…While individual trajectories are important for the understanding of child's cognitive development, existing theories highlight the role of social interaction in child's learning (Bandura, 1971 ; Vygotsky, 1978 ; Tomasello, 1995 ). For young children, the development of effective strategies for problem-solving is often associated to scaffolding from the social environment (Tomasello, 1995 ; Cragg and Chevalier, 2012 ); collaboration is particularly beneficial for low-ability children when there is an ability asymmetry (Sills et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%